2006
DOI: 10.1111/j.1525-1438.2006.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer in pregnancy: a clinicopathologic analysis of 22 cases and review of the literature

Abstract: The aim of this study was to summarize our experience of ovarian cancer diagnosed during pregnancy, to review the literature concerned, and to discuss the rationale for therapy. Twenty-two patients of ovarian malignancies complicating pregnancy were treated at Peking Union Medical College Hospital between 1985 and 2003. Data on treatment and follow-up were reviewed, and their outcomes were analyzed by survival analysis. The incidence of ovarian carcinoma complicating pregnancy in the series was 0.073/1000 preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 34 publications
3
72
1
7
Order By: Relevance
“…The prognosis of maternal ovarian cancers is similar to those in non-pregnant women in the reproductive age [20]. Suboptimal therapy and initial advanced stage of disease as a result of delayed diagnosis in some pregnant women are associated with worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of maternal ovarian cancers is similar to those in non-pregnant women in the reproductive age [20]. Suboptimal therapy and initial advanced stage of disease as a result of delayed diagnosis in some pregnant women are associated with worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no definitive guidelines in the literature regarding the management of maternal ovarian cancer, with the exception of summaries of international consensus meetings (8,9). Subsequently, a number of studies have reported and discussed numerous issues pertaining to this issue (10)(11)(12)(13)(14). We have focused on results-oriented points including the incidence, diagnosis, histopathology, treatment and maternal or neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Immature teratoma is frequent in young women, 1 and usually present with subacute abdominal pains due to rapid growth of a large, unilateral tumor undergoing capsular distention, hemorrhage or necrosis. In more advanced diseases, ascites may develop and cause abdominal distention.…”
Section: Discussionmentioning
confidence: 99%
“…1 The reported incidence of pregnancy complicated by an immature teratoma is 0.07%. 2 This tumor is highly malignant and may threaten the life of the mother.…”
Section: Introductionmentioning
confidence: 99%